Investigating Students’ Perception on The Use of Google Classroom During Pandemic in Learning English - Adelia Fernanda; Supriusman Supriusman; Afrianto Daud; Michelle Espinoza Lobos (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2022)
This research aims to investigate students' perception on using Google Classroom during the COVID-19 pandemic in learning English. The subjects of this study were all eighth grade students of Islamic Junior High School (SMP Islam) As-Shofa Pekanbaru with the total of 105 students. This research was conducted by using a quantitative method. Data were collected using online questionnaire. The result showed that there were three indicators on using Google Classroom during COVID-19 pandemic in learning English; in terms of its usefulness, easiness and satisfaction. The result of the research shows that the average mean score was 3.72 which means students had highly positive response. It indicates that most students gave positive responses toward using Google Classroom during COVID-19 pandemic in learning English, most of students was agree that Google Classroom was easy to use and have good performance to use Google Classroom in learning English because Google Classroom facilitate the students to save and get materials, assignment, information and announcement, enhances students’ learning productivity, improves students’ performance, and students are satisfied and interested in learning English. This study implies that Google Classroom can be considered as one of alternative learning platforms that can be used by schools to learn English during pandemic situation and other emergency situations.